Phosphorus binding dynamics in the aluminum floc layer of Half Moon Lake, Wisconsin. (3rd April 2017) - James, William F.
ABSTRACT: James WF. 2017. Phosphorus binding dynamics in the aluminum floc layer of Half Moon Lake, Wisconsin. Lake Reserve Manage. 33:130–142. Half Moon Lake is a shallow oxbow located in Eau Claire, Wisconsin. Eutrophic to hypereutrophic conditions and cyanobacteria blooms driven primarily by sediment internal phosphorus (P) loading led to a buffered aluminum sulfate treatment in 2011. Aluminum (Al) dosage was based on the redox-sensitive P (redox-P) concentration in the upper 4 cm sediment layer. The west arm was treated with 150 g/m 2 to sequester 1 to 5 mg/g redox-P while the east arm was treated with 75 g/m 2 to bind an order of magnitude lower redox-P concentration (0.15 mg/g). Four years after treatment, the Al floc layer was positioned on top of the original sediment surface due to density differences between sediment and the Al floc. Rather than sinking or mixing into the sediment, P binding has occurred primarily via upward diffusive P flux into the Al floc layer. Changes in vertical P profiles over time suggested that the Al floc in the western arm has bound only ∼60% of this upward diffusive P flux, whereas the other portion has become associated with Fe and now potentially contributes to the lake P budget through redox-driven recycling pathways. The east arm Al floc layer has sequestered ∼90% of the much lower upward diffusive P flux. Laboratory-derived anaerobic diffusive P fluxes in the west arm have increased from near 0 in 2011 to ∼3.7 mg/m 2 d in 2015. P binding inefficiency may be attributed to Al polymerization to a more ordered crystalline structure over time in the absence of exposure to sediment P.